Inactivation of the mitotic checkpoint as a determinant of the efficacy of microtubule-targeted drugs in killing human cancer cells - Eric A. Lee; Michael K. Keutmann; Melissa L. Dowling; Eleanor Harris; Gordon K. Chan; Gary D. Kao (2004)
Abstract Drugs that disrupt microtubule dynamics include some of the most important of cancer chemotherapies. While these drugs, which include paclitaxel (Taxol), are known to invoke the mitotic checkpoint, the factors that determine cancer cell killing remain incompletely characterized. Cells that are relatively resistant to killing by these drugs block robustly in mitosis, whereas cells sensitive to killing block only transiently in mitosis before undergoing nuclear fragmentation and death. Passage through mitosis was an absolute requirement of drug-induced death, because death was markedly reduced in cells blocked at both G1-S and G2. Cell killing was at least in part linked to the absence or inactivation of BubR1, a kinetochore-associated phosphoprotein that mediates the mitotic checkpoint. Sensitivity to paclitaxel correlated with decreased BubR1 protein expression in human cancer cell lines, including those derived from breast and ovarian cancers. Silencing of BubR1 via RNA interference inactivated the mitotic checkpoint in drug-resistant cells, and reversed resistance to paclitaxel and nocodazole. Together, these results suggest that the mitotic checkpoint is an important determinant of the efficacy of microtubule-targeting drugs in killing cancer cells, potentially providing novel targets for increasing treatment efficacy.